2013
DOI: 10.1111/ped.12163
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic silent carditis: Echocardiographic diagnosis and prognosis of long‐term follow up

Abstract: It is suggested that Doppler echocardiography be performed in all patients with suspected acute rheumatic fever for early detection of SC. Echocardiography should be used as a diagnostic criterion in order not to miss a diagnosis of SC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In one study, the prevalence of subclinical carditis following the first episode of ARF was 18% and half of the patients had persistence or deterioration of disease 2–23 months later 178 . Studies by Araujo and colleagues 179 and Pekpak and colleagues 180 reported that the proportion of patients with subclinical ARF who had persistence of carditis at least 1 year later was 72% and 55%, respectively.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…In one study, the prevalence of subclinical carditis following the first episode of ARF was 18% and half of the patients had persistence or deterioration of disease 2–23 months later 178 . Studies by Araujo and colleagues 179 and Pekpak and colleagues 180 reported that the proportion of patients with subclinical ARF who had persistence of carditis at least 1 year later was 72% and 55%, respectively.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Unless in severe pulmonal hypertension due to various causes, Marfan syndrome and aortic aneurism, surgery should be performed electively. However, intensive care is needed during postpartum period [33].…”
Section: Discussionmentioning
confidence: 99%
“…34 Moreover, we previously reported the progression of valvular regurgitation in 6 children (30%) among 20 children who were diagnosed with subclinical rheumatic heart disease, after a follow-up of 43.4 ± 25 months. 41 Therefore, we suggest long-term penicillin prophylaxis in children with subclinical rheumatic heart disease. It is known that secondary prophylaxis improves the prognosis of this disease and prevents recurrence.…”
Section: Discussionmentioning
confidence: 99%